2015
DOI: 10.1002/acr.22601
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Early Work Experiences of Young Adults With Rheumatic Disease: An Examination of Absenteeism, Job Disruptions, and Productivity Loss

Abstract: Objective. To examine work absenteeism, job disruptions, and perceived productivity loss and factors associated with each outcome in young adults living with systemic lupus erythematosus (SLE) and juvenile arthritis (JA). Methods. One hundred forty-three young adults, ages 18-30 years with SLE (54.5%) and JA (45.5%), completed an online survey of work experiences. Demographic, health (e.g., fatigue, disease activity), psychosocial (e.g., independence, social support), and work context (e.g., career satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Understanding health from the individual's perspective is a prerequisite for reaching the goal of good health in cooperation with the healthcare team. Health among young adults has been described in general (Ainsworth & Ananian 2013, Breiner et al 2014, Park et al 2014 and from the perspectives of living with various disabilities (Blomquist 2006) or diseases (Patterson et al 2012, Ferris et al 2015, Jetha et al 2015. However, while previous research on MD has focused on children and/or parent proxy reports (Bray et al 2010, Lim et al 2014, Opstal et al 2014 adolescents (Pehler & Craft-Rosenberg 2009, Parkyn & Coveney 2013, adults (Bostr€ om & Ahlstr€ om 2004) or young men living Duchenne MD (Dreyer et al 2010, Abbott & Carpenter 2014, there is a gap in knowledge about health perceptions among young adults living with LGMD2.…”
Section: What Are the Key Findings?mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding health from the individual's perspective is a prerequisite for reaching the goal of good health in cooperation with the healthcare team. Health among young adults has been described in general (Ainsworth & Ananian 2013, Breiner et al 2014, Park et al 2014 and from the perspectives of living with various disabilities (Blomquist 2006) or diseases (Patterson et al 2012, Ferris et al 2015, Jetha et al 2015. However, while previous research on MD has focused on children and/or parent proxy reports (Bray et al 2010, Lim et al 2014, Opstal et al 2014 adolescents (Pehler & Craft-Rosenberg 2009, Parkyn & Coveney 2013, adults (Bostr€ om & Ahlstr€ om 2004) or young men living Duchenne MD (Dreyer et al 2010, Abbott & Carpenter 2014, there is a gap in knowledge about health perceptions among young adults living with LGMD2.…”
Section: What Are the Key Findings?mentioning
confidence: 99%
“…, Jetha et al . ). However, while previous research on MD has focused on children and/or parent proxy reports (Bray et al .…”
Section: Introductionmentioning
confidence: 97%
“…Since JIA often persists into adulthood [3][4][5], patients with JIA are likely to encounter difficulties in their working life. Earlier studies showed inconsistencies regarding employment rates and educational achievements of patients with JIA in comparison to the general population [6][7][8][9][10][11]. This ranges from no differences in occupational outcomes between JIA and comparison groups [7] to an alarming 32% of patients with JIA who are either disabled, receive a disability pension, are on sick leave or undergoing rehabilitation treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some stated that complaints were not always taken seriously during a part-time job, while for others adjustments were made in the workload. Workload adjustments were easily implemented when colleagues were friends or family, as these were considered more supportive (quotations [11][12][13].…”
mentioning
confidence: 99%
“…Other research were able to show an association between arthritis and increased employment rates [15–17]. However, for the general description of the transition process into adulthood, the results of several studies suggest, that there is no significant difference between patients with rheumatic disease and their healthy peers [18]. …”
Section: Introductionmentioning
confidence: 99%